2007
DOI: 10.1007/s00436-007-0584-x
|View full text |Cite
|
Sign up to set email alerts
|

The intestinal nematode Trichuris arvicolae affects the fecundity of its host, the common vole Microtus arvalis

Abstract: Parasites have detrimental effects on host fitness. Consequently, they play a major role for host population dynamics. In this study, we investigated experimentally the impact of the nematode Trichuris arvicolae on the reproduction of its host, the common vole Microtus arvalis. Wild common voles were trapped in east of France and reared in standardized conditions before being experimentally infected. Infection with Trichuris arvicolae did not affect host consumption of food or water. Parasitized females gave b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…We were motivated by two major observations. First, several studies demonstrate that parasites negatively influence reproduction in rodents (Neuhaus 2003, Deter et al 2007, Vandegrift et al 2008, Hillegass et al 2010, suggesting that a decrease in parasitism could explain the increase in mouse reproduction that we have observed in burned forest (Zwolak andForesman 2008, Zwolak et al 2012). Secondly, we also had reasons to suspect that fire could suppress parasite populations.…”
Section: Introductionmentioning
confidence: 79%
“…We were motivated by two major observations. First, several studies demonstrate that parasites negatively influence reproduction in rodents (Neuhaus 2003, Deter et al 2007, Vandegrift et al 2008, Hillegass et al 2010, suggesting that a decrease in parasitism could explain the increase in mouse reproduction that we have observed in burned forest (Zwolak andForesman 2008, Zwolak et al 2012). Secondly, we also had reasons to suspect that fire could suppress parasite populations.…”
Section: Introductionmentioning
confidence: 79%
“…However, we can hypothesize that in natural conditions, the decrease of life span induced by parasites or other extrinsic mortality factors leads to a lower number of breeding opportunities and to a lower life-time reproductive success, especially for short-lived species exposed to high extrinsic mortality factors (Christe et al 2006). Moreover, experimental evidence suggests that endoparasitism reduces the reproductive success of breeding common voles (Deter et al 2007). …”
Section: Discussionmentioning
confidence: 99%
“…Reduction of fecundity due to ectoparasitism has been documented several times (e.g. Deter et al 2007 ;Møller, 1997 ;Neuhaus, 2003 ;Saino et al 1998), whereas evidence of the negative effect of ectoparasites on life span and thus on the reproductive life-time is scarce (but see Brown et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Here, we used gastrointestinal helminths (GIH) communities in commensal rodents to test some predictions relating animal invasion success and parasitism. Besides of their known regulatory effects on rodent fitness (Deter et al 2007) and population dynamics (Vandegrift & Hudson 2009), GIH were found to be highly diversified and prevalent in rodent populations in Senegal (Brouat et al 2007). A loss or reduction of parasites by invasive rodents along their invasion route was expected under the PR hypothesis, and/or an increase of parasitism in native rodents when they co-occurred with invasive ones under the SO or SB hypotheses.…”
mentioning
confidence: 96%